Zombieland [videorecording (DVD)] - Harrelson, Woody; Eisenberg, Jesse, 1983-; Stone, Emma, 1988-; Breslin, Abigail, 1996- (Sony Pictures Home Entertainment, 2010)
In a world that has become overrun with zombies, two men must figure out how to survive. Wimpy Columbus is afraid of his own shadow, while Tallahassee is the biggest, baddest, gun-toting zombie-slayer who ever lived. When they meet two sisters, Wichita and Little Rock, the four strike out for an amusement park that is said to be zombie-free. This mismatched group will have to rely on each other to survive, which could be worse than surrendering to the zombies.